Working with adult abuse: a training manual for people working with vulnerable adults - Pritchard, Jacki (JKP resource materials, 2007)
Purpose of the manual and how to use it -- History, current guidance, and principles -- What is adult abuse? -- Recognising adult abuse -- Handling disclosure -- Investigating adult abuse -- Case conferences -- Risk assessment developing protection plans -- Recording -- The abuse of older people -- The abuse of younger adults -- The abuse of Black and minority ethnic people